2015
DOI: 10.3109/0886022x.2015.1056064
|View full text |Cite
|
Sign up to set email alerts
|

Association between colchicine resistance and vitamin D in familial Mediterranean fever

Abstract: Although colchicines are the only effective treatment of familial Mediterranean fever (FMF), resistance to colchicines (CR) which is observed in up to 30% of the patients is still a problem. Clinically, resistance to colchicine is defined as three or more attacks within the last 6 months period while using ≥2 mg/day colchicine. Previous studies have shown decreased vitamin D levels in FMF patients compared with healthy controls. The aim of this study is to evaluate whether vitamin D levels differ between CR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Karatay et al 3 reported low vitamin D levels in patients with Behcet's disease and also demonstrated a strong relationship between colchicine use and low serum vitamin D levels as in our study. Similarly, Ö zer et al 1 reported a significantly higher mean colchicine dose in resistant patients, in whom lower vitamin D levels were observed. To date, the exact mechanism of colchicine is unknown.…”
Section: Colchicine Resistance and Low Vitamin D In Familial Mediterrmentioning
confidence: 84%
See 1 more Smart Citation
“…Karatay et al 3 reported low vitamin D levels in patients with Behcet's disease and also demonstrated a strong relationship between colchicine use and low serum vitamin D levels as in our study. Similarly, Ö zer et al 1 reported a significantly higher mean colchicine dose in resistant patients, in whom lower vitamin D levels were observed. To date, the exact mechanism of colchicine is unknown.…”
Section: Colchicine Resistance and Low Vitamin D In Familial Mediterrmentioning
confidence: 84%
“…We read with interest the study by Ö zer et al 1 evaluating the association between colchicine resistance and vitamin D levels in familial Mediterranean fever (FMF).…”
Section: Colchicine Resistance and Low Vitamin D In Familial Mediterrmentioning
confidence: 99%
“…90 Vitamin D deficiency in FMFwas proposed to contribute to the lack of response to colchicine. 87 Blood group A had 1.5-fold higher incidence of FMF and a better response to colchicine treatment than the non-A blood group, while patients in the O blood group prominently exhibited colchicine resistance. 91 Cellular transport of colchicine is mediated by the P-glycoprotein (P-gp) efflux pump encoded by the multiple drug resistance-1 gene.…”
Section: Re S Is Tan Ce To Colchi Cine Ther Apymentioning
confidence: 89%
“…Despite regular use, 10%-30% of patients with FMF do not respond to colchicine, even when used at the highest tolerable dose. [83][84][85][86][87] There is no standard, validated definition for colchicine resistance, and proper definitions for attack-free periods and persistence of high acute phase reactants are still lacking. 85 Colchicine does not exert an immediate effect when administered during an acute attack of FMF, suggesting that higher concentrations and prolonged treatment periods may be required for to achieve an effect on neutrophil function and for a resulting therapeutic effect.…”
Section: Re S Is Tan Ce To Colchi Cine Ther Apymentioning
confidence: 99%
“…[ 44 ] 2017 ≥1 Attacke/Monat über 3 Monate Ozer, I. et al. [ 45 ] 2015 ≥3 Attacken in 6 Monaten Ozkan, S. et al. [ 46 ] 2017 Schwere, häufige Attacken und/oder erhöhte Entzündungsparameter Pecher, A.C. et al.…”
unclassified